2012
DOI: 10.4238/2012.september.19.6
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality traits of four commercial pig crossbreeds in China

Abstract: ABSTRACT. We evaluated carcass and meat quality traits of two Chinese native crossbreeds Landrace x Meishan (LM) and Duroc x (Landrace x Meishan) (DLM) and two foreign crossbreeds Duroc x (Landrace x Yorkshire) (DLY) and PIC (an imported five-way crossbreed). One hundred and twenty weaned pigs (half castrated males and half females) were reared and slaughtered at a predestinated slaughter age. The general carcass and meat quality traits were measured and analyzed. The DLY and PIC crosses had significantly heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…The loin eye area was measured at the last rib level and calculated based on the loin eye height and width with 0.7 as the coefficient (Dai et al 2009). The fat thickness of the first and last ribs, and the last lumbar vertebra were measured using a vernier calliper (Jiang et al 2012). The average of those three measurements was used as the back-fat thickness.…”
Section: Carcase Traitsmentioning
confidence: 99%
“…The loin eye area was measured at the last rib level and calculated based on the loin eye height and width with 0.7 as the coefficient (Dai et al 2009). The fat thickness of the first and last ribs, and the last lumbar vertebra were measured using a vernier calliper (Jiang et al 2012). The average of those three measurements was used as the back-fat thickness.…”
Section: Carcase Traitsmentioning
confidence: 99%
“…The average introgression level was determined to be approximately 33% [21]. A few genome-wide studies have shown that introgression has also occurred from European to Asian pigs [22][23][24]. However, the genomic differences caused by introgression were not examined, and the functions affected by the altered genomic regions are also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, pork crossbreeding is perceived as method helping to improve meat quality (Jiang et al 2012). In Poland, production of pork crossbreed was based on crossing Polish Large White or Polish Landrace dams with Pietrain, Duroc or Hampshire sires (Blicharski and Hammermeister 2013).…”
Section: Introductionmentioning
confidence: 99%